Patterns of rhetorical organization in The Jakarta Post opinion articles - Dwi Indarti (Universitas Syiah Kuala, 2018)
Opinion articles are part of a professional discourse genre that can be found in newspapers. These articles are separated from news pages and written for the public, so they contain a variety of cultural backgrounds. This study looked at 151 opinion articles published in The Jakarta Post of the March 2016 editions. Shi and Kubota’s (2007)four pattern of rhetorical organization was adapted as the theoretical framework for the present study. The results of this study showed that the overall rhetorical pattern of The Jakarta Post opinion articles is a three-part structure of introduction, body and conclusion paragraphs. In term of the placing of the thesis statement, 47% of non-native writers and 38% of native writers put the thesis statement in the introduction part with a single sentence paragraph or two short single-sentence paragraphs, and 38% of non-native writers and 40% of native writers wrote the introduction part with two or more multi-sentence paragraphs, and put the thesis statement at the end of them. Only 8% of non-native writers and 5% of native writers put the thesis statement in the body part, while 7% of non-native writers and 17% of native writers put the thesis statement in the conclusion. Generally, there was a slight difference between native and non-native writers in terms of the placement of thesis statement, where the non-native writers tended to use a single sentence paragraph as the thesis statement as well as to begin the essays, while native writers preferred to use two or more multi sentence paragraphs. This study proves that professional writings such as newspaper opinion articles follow the English rhetorical conventions; deductive, logical, and direct style as represented in the three-part structure.